Trends in colorectal cancer screening over time for persons with and without chronic disability. Issue 3 (July 2016) - Iezzoni, Lisa I.; Kurtz, Stephen G.; Rao, Sowmya R.
Abstract: Background: Persons with disabilities have often experienced disparities in routine cancer screening. However, with civil rights protections from the 1990 Americans with Disabilities Act, such disparities may diminish over time. Objective: To examine whether disability disparities exist for colorectal cancer screening and whether these screening patterns have changed over time. Methods: We analyzed National Health Interview Survey responses from civilian, non-institutionalized U.S. residents 50–75 years old from selected years between 1998 and 2010. We specified 7 chronic disability indicators using self-reported functional impairments, activity/participation limitations, and expected duration. Separately for women and men, we conducted bivariable and multivariable logistic regression analyses examining associations of self-reported colorectal cancer screening services with sociodemographic factors and disability type. Results: Patterns of chronic disability differed somewhat between women and men; disability rates generally rose over time. For both women and men, colorectal cancer screening rates increased substantially from 1998 through 2010. Over time, relatively few statistically significant differences were reported in colorectal cancer screening rates between nondisabled persons and individuals with various disabilities. In 2010, reported screening rates were generally comparable between nondisabled and disabled persons. In the few statistically significant differences, persons with disabilities almost always reported higher colorectal cancer screening rates than nondisabled individuals. Conclusions: According to national survey data, reported use of colorectal cancer screening is similar between nondisabled persons and individuals with a variety of different disability types. Despite physical demands of some colorectal cancer screening tests, disparities do not appear between populations with and without disability.